Cooperation with Health Professionals during the Pandemic of COVID 19 - Niroula, Ghanashyam (Dhaulagiri Journal of Sociology and Anthropology, 2020)
The article presents light on the issues of cooperation with health workers during the COVID 19. Coronavirus pandemic has become one of the challenges to humankind and it caused devastating effects in almost all countries of the world. The purpose of the paper is to analyze how important the role of people’s cooperation with health workers is during the coronavirus pandemic. The theoretical concept related to humanism and social identity theory is discussed to understand individual and group’s collective effort to increase cooperation in the society during the pandemic. Subsequently, different events of cooperation among people and health workers and other incidents depicting stigma and discrimination in Nepal and other places during the COVID 19 pandemic are discussed based on a review of literatures.